Comprehensive analysis of the rostral and caudal cerebral artery branching patterns in the dromedary camel (Camelus dromedarius) - Al Aiyan, Ahmad; Balan, Rinsha (Frontiers in Veterinary Science, 2024)
Introduction In mammals, the cerebral cortex depends on a robust blood supply for optimal function. The rostral and caudal cerebral arteries are critical for supplying the cerebrum. This study presents the first detailed anatomical description of the rostral and caudal cerebral arteries of dromedary camels (Camelus dromedarius), including their origins, routes, and complex branching patterns. Methods A sample of 55 heads from male dromedary camels aged 2–6 years was analyzed using advanced casting techniques with various casting materials to provide precise visualization of these arterial structures. Results The rostral cerebral arteries originate dorsally from the rostral epidural rete mirabile (RERM), while the caudal cerebral arteries arise from the caudal communicating artery, which is another branch of the RERM. Both sets of arteries give rise to multiple cortical branches responsible for supplying the medial aspects of the frontal, parietal, and temporal lobes, as well as the medial and caudal regions of the occipital lobes. Conclusion This study significantly expands our understanding of the cerebrovascular anatomy of dromedary camels. Our findings have potential implications for veterinary medicine in the diagnosis and treatment of neurological disorders in camels and may offer insights into broader comparative neuroscience research.